MOTIVASI BERPRESTASI PENDAMPING SOSIAL PROGRAM KELUARGA HARAPAN (STUDI KASUS PELAKSANAAN FAMILY DEVELOPMENT SESSION DI KABUPATEN GRESIK) - Endah Setiyowati; Umi Dayati; Sri Wahyuni (Jurnal Pendidikan Nonformal, 2021)
Social Assistants for Family Hope Program (hereinafter referred to PKH / Program Keluarga Harapan) are individuals who have gone through a selection or recruitment process and a series of education and training as professionals in carrying out program assistance activities held by the Ministry of Social Affairs. Social Assistants for PKH who have high motivation are expected to be able to utilize all natural and human resources in the area where they do this sosial assistance. They play a role as an medium in intervening the economic issues of Beneficiary Families (KPM) in each activity of Family Development Session (FDS). Thus, the implementation of PKH, especially FDS has been one of the transfer of learning both knowledge and skills among its social assitants and beneficiary families in the realization of independence and prosperity.            The focus of this research is to find out how the achievement motivation and actualization of PKH social assistants in the implementation of FDS. This research used a qualitative approach with a case study type. Data were collected using interview, observation, and documentation techniques. Data validity was tested using technique and source triangulations. The data were then analyzed using Spradely’s domain and taxonomy model.            The results showed that: (1) PKH social assistants, in addition to providing daily assistance to beneficiary families’ social issues, also carry out their main duties and functions every month, one of which is FDS as an activity performed in a structured manner in accordance with the modules provided. In prior, PKH social assistants are educated and trained so that their assistance works as expected. (2) PKH social assistants carry out a number of self-actualization activities in several ways, namely (a) PKH implementation; (b) FDS module implementation, and (c) self-capacity. (3) There are 2 main factors influencing the growth of PKH social assistants’ achivement-motivation, namely instrinsic and extrinsic. Intrinsic factors consist of ideals and interests whereas extrinsic factors consist of (a) appreciation; (b) work environment; (c) independence, and (d) parenting